Hypothesis: Could Excessive Fructose Intake and Uric Acid Cause Type 2 Diabetes? - Johnson, Richard J. (The Endocrine Society, 2009)
We propose that excessive fructose intake (>50 g/d) may be one of the underlying etiologies of metabolic syndrome and type 2 diabetes. The primary sources of fructose are sugar (sucrose) and high fructose corn syrup. First, fructose intake correlates closely with the rate of diabetes worldwide. Second, unlike other sugars, the ingestion of excessive fructose induces features of metabolic syndrome in both laboratory animals and humans. Third, fructose appears to mediate the metabolic syndrome in part by raising uric acid, and there are now extensive experimental and clinical data supporting uric acid in the pathogenesis of metabolic syndrome. Fourth, environmental and genetic considerations provide a potential explanation of why certain groups might be more susceptible to developing diabetes. Finally, we discuss the counterarguments associated with the hypothesis and a potential explanation for these findings. If diabetes might result from excessive intake of fructose, then simple public health measures could have a major impact on improving the overall health of our populace.